Humanity and Disaster: Youth Altruism of ACT (Aksi Cepat Tanggap) in Disastrous Mitigation (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
Along with advances in technology and communication at this time, more individuals who are selfish or have a reduced sense of helping each other, especially the lack of involvement of young people in social wellbeing actions, most of whom are socially indifferent, pragmatic and a little hedonistic. By using Pierre Bourdieu's concept of social practice, which focuses more on social capital factors, it will be easier to identify the altruistic young volunteers of ACT East Java. The research method uses field research which uses qualitative research methods. The method used by researchers in finding and collecting data is documentation, observation, and interviews. In this study someone who shows altruistic behavior is a person who has a level of religiosity, that there is a relationship between religiosity and altruism behavior, where a young volunteer ACT East Java, where most of the active members have religiosity will provide help voluntarily, help without expecting any form of reward and besides that, there is also spiritual satisfaction when helping sincerely.